Апоптическая децеллюляризация, как способ предотвращения деструктивных изменений в биологических протезах сердечных клапанов - Петрова, М.В. (Таврический медико-биологический вестник, 2012)
Проведено дослідження з отримання девіталізованого сполучнотканинного матриксу клапанів серця за допомогою запуску апоптозу. У якості девіталізуючого використовувався 10мМ розчин ЕДТА. Ініціацію апоптозу можна вважати вдалою, але кількість апоптичних клітин не однакове для різних структур ксенографту. Bioartificial grafts of heart valves and vessels should have certain properties, moreover, be steady to calcification. This research was aimed to produce biomodificated cardiovascular graft by decellularisation of heart valve connective tissue matrix. To achieve decellularisaton 10 mM EDTA solution was used. It seems, that decellularisaton is successful, but number of apoptotic cells are not identical in different parts of graft.